2021
DOI: 10.3389/fonc.2021.710767
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methylandenosine-Related lncRNAs Predict Prognosis and Immunotherapy Response in Bladder Cancer

Abstract: Both lncRNAs and the N6-methyladenosine (m6A) modification are key regulators of tumorigenesis and innate immunity. However, little is known about the m6A modification of lncRNAs and their clinical and immune relevance in bladder cancer. In this study, we identified m6A-related lncRNAs using Pearson correlation analysis in The Cancer Genome Atlas (TCGA) and the IMvigor210 datasets. Next, univariate Cox regression was performed using the TCGA dataset to filter prognostic m6A-related lncRNAs, which were further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…In ROC curves of risk scores and traditional clinical factors, the area of risk scores under the ROC curve was higher than our conventional clinical indicators. Compared with current models, such as model of N6-methylandenosine-related lncRNAs, our model predicts 1, 3, and 5-year survival rates with higher accuracy than N6-methylandenosine-related lncRNAs model ( 22 ). All of these results showed the rationality and superiority of our 7 lncRNAs model.…”
Section: Discussionmentioning
confidence: 87%
“…In ROC curves of risk scores and traditional clinical factors, the area of risk scores under the ROC curve was higher than our conventional clinical indicators. Compared with current models, such as model of N6-methylandenosine-related lncRNAs, our model predicts 1, 3, and 5-year survival rates with higher accuracy than N6-methylandenosine-related lncRNAs model ( 22 ). All of these results showed the rationality and superiority of our 7 lncRNAs model.…”
Section: Discussionmentioning
confidence: 87%
“…M6A is the most common internal RNA modification in several species ( Jia et al, 2011 ). The m6A lncRNA alteration and its involvement in BLCA patients are rarely reported ( Zhang et al, 2021b ). Zhou et al (2021) reported that FTO promoted tumor development in BLCA via the FTO/miR-576/CDK6 axis in an m6A-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, downregulation of METTL14 in rectal cancer is correlated with poor outcome in patients [112]. When it comes to lower-grade glioma, lung adenocarcinoma, breast cancer, and bladder cancer, risk models including m 6 A-mediated lncRNAs were built, revealing an effective value in predicting the prognoses [113][114][115][116]. More recently, Shen et al, conducted comprehensive analyses for the predictive value of 23 m 6 A regulators and 83 mRNAs and noncoding RNAs among 9804 pan-cancer samples [117].…”
Section: Acting As Diagnostic Markers and Prognostic Predictorsmentioning
confidence: 99%